2015
DOI: 10.1155/2015/469750
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Chemosensory Detection of Negative Emotions in Congenital Blindness

Abstract: It is generally acknowledged that congenitally blind individuals develop superior sensory abilities in order to compensate for their lack of vision. Substantial research has been done on somatosensory and auditory sensory information processing of the blind. However, relatively little information is available about compensatory plasticity in the olfactory domain. Although previous studies indicate that blind individuals have superior olfactory abilities, no studies so far have investigated their sense of smell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 39 publications
(45 reference statements)
4
33
1
Order By: Relevance
“…It should be noted that the different level of sensory compensation for audition and olfaction in the case of mate selection might have resulted from other factors. Contrary to a number of studies consistently reporting superior auditory processing among blind people (Lessard, Paré, Lepore, & Lassonde, 1998 ; Lewald, 2002 , for a review, see Kupers & Ptito, 2014 ), results of studies on objective olfactory sensitivity often show that it is not significantly higher among blind people (Guducu, Oniz, Ikiz, & Ozgoren, 2016 ; Luers et al, 2014 ; Sorokowska, 2016 ; for a review, see Kupers & Ptito, 2014 ), even if they report higher olfactory awareness (Beaulieu-Lefebvre et al, 2011 ; Ferdenzi et al, 2010 ) and can discriminate negative emotions based on body odor samples (Iversen et al, 2015 ). Thus, given similar performance of blind and sighted people in various smell tasks, olfactory sensory compensation may not be particularly pronounced in visual impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the different level of sensory compensation for audition and olfaction in the case of mate selection might have resulted from other factors. Contrary to a number of studies consistently reporting superior auditory processing among blind people (Lessard, Paré, Lepore, & Lassonde, 1998 ; Lewald, 2002 , for a review, see Kupers & Ptito, 2014 ), results of studies on objective olfactory sensitivity often show that it is not significantly higher among blind people (Guducu, Oniz, Ikiz, & Ozgoren, 2016 ; Luers et al, 2014 ; Sorokowska, 2016 ; for a review, see Kupers & Ptito, 2014 ), even if they report higher olfactory awareness (Beaulieu-Lefebvre et al, 2011 ; Ferdenzi et al, 2010 ) and can discriminate negative emotions based on body odor samples (Iversen et al, 2015 ). Thus, given similar performance of blind and sighted people in various smell tasks, olfactory sensory compensation may not be particularly pronounced in visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of social olfactory perception, a small number of experiments have shown that both blind adults (Beaulieu-Lefebvre, Schneider, Kupers, & Ptito, 2011 ) and blind children (Ferdenzi, Coureaud, Camos, & Schaal, 2010 ) report stronger odor awareness than sighted peers, particularly in response to odors that naturally emanate from or are associated with human bodies. Further, congenitally blind people were reported to exhibit superior performance when discriminating negative emotions based on body odor samples (Iversen, Ptito, Møller, & Kupers, 2015 ). Moreover, studies of auditory social perception reported that blind participants were able to perform voice-based size estimation as accurately as sighted participants (Pisanski, Oleszkiewicz, & Sorokowska, 2016 ; Pisanski, Feinberg, Oleszkiewicz, & Sorokowska, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In light of previous evidence, we expected that blind individuals would recognize emotions as accurately as sighted individuals, if not better (see Iversen et al, 2015; Kitada et al, 2013; Klinge et al, 2010). In this scenario, preservation of hemispheric lateralization would presuppose that emotion cues garnered from other sensory modalities (e.g., auditory, haptic, and olfactory domains) may be sufficient for the specialization of related emotion processing brain networks.…”
mentioning
confidence: 93%
“…In contrast to sighted controls, blind individuals must rely more heavily on hearing and touch to capture salient cues from non-visual environment, which induces compensatory changes in the abilities of non-visual perception. In fact, abundant studies have demonstrated that blind people have altered auditory181920, olfactory2122 and tactile perceptual abilities232425, as well as improved non-visual attentional2627 and work memory performance2628, etc. In addition to the non-visual behavioural changes, cross-modal involvement of the visual areas in processing non-visual stimuli were also identified by early studies, which included tactile2930313233, auditory2934353637, and olfactory38 perception, and even higher cognitive processing driven by these non-visual stimuli such as language3940, attention2627 and working memory2628.…”
mentioning
confidence: 99%